Ecological Interaction between Insect Pests, Climatic Factors and Plant Traits on Abundance of Beneficial Insects in Paddy Field - R, Norazliza; Z, Mohd Rasdi; I, Fauziah; R, Ismail; M. N, Mohd Hanysyam (Asian Journal of Agriculture and Rural Development, 2016)
The presences of beneficial insects in the paddy field are very important for the ecological systems of paddy field as those insects could help managing the population of the pests. Hence, it will reduce the dependence on pesticides usage to combat the population of insect pests. This study was aimed to study on ecological interaction between environmental factors such as insect pests, plant height, rainfall, temperature and humidity with abundance of beneficial insects in paddy field of Sungai Burong, Tanjung Karang, Selangor for two seasons of paddy planting. Low number of insects composition were recorded in paddy field at Sungai Burong during the vegetative phase and highest during the reproductive and maturity phases for two seasons of paddy planting. The trend of mean composition of insects were gradually increasing from vegetative to maturity phases while, the ecological interaction between insect pests, climatic factors and plant traits were acceptable as good predictor for all beneficial insects collected in this study namely Zygoptera, Gerridae, Coccinellidae and Staphylinidae except for Anisoptera. Therefore, consideration on several stated factors by maintaining or conserving ecology and controlling practices in good manner in paddy field has high potential and more reliable to control insect pests effectively using beneficial insects.